Structure characterization and antioxidant activity analysis of polysaccharides from Lanzhou Lily - Gao, Dandan; Chen, Hong; Liu, Honghai; Yang, Xuhua; Guo, Penghui; Cao, Xin; Cai, Yong; Xu, Hongwei; Yang, Jutian (Frontiers in Nutrition, 2022)
Lanzhou Lily (Lilium davidii var. unicolor) is a traditional medicinal plant and popular edible vegetable bulb in China. In this study, the polysaccharides of Lanzhou Lily (LLPs) were extracted by polyethylene glycol-based ultrasonic-assisted enzymatic extraction (UAEE) method. The optimum process conditions were obtained by single-factor experiments and response surface methodology (RSM). Then, the preliminarily structure of LLPs was characterized by HPLCFT-IR, and SEM, and its antioxidant activities were evaluated. The results showed that LLPs yield reached 14.75% under the optimized conditions: E/S ratio 1400 U/g; pH 5.0, ultrasonic time 30 min; and ultrasonic temperature 50 °C. The LLPs has pyranoid ring, uronic acid, and the characteristic absorption peaks of -OH, C = O, and C-O-CH. The results of scanning electron microscope showed that the LLPs had irregular distribution, dispersed structure, and many holes. The HPLC analysis showed that the LLPs were heteropolysaccharide containing galactose (6.36%), glucose (76.03%), rhamnose (2.02%), and arabinose (7.09%). Moreover, the LLPs showed obvious antioxidant effect in vitro.